Resistance Redux. Issue 9 (September 2017) - Mumby, Dennis K.; Thomas, Robyn; Martí, Ignasi; Seidl, David
The last 15 years have witnessed renewed interest in resistance in and around organizations. In this essay, we offer a conceptual framework to thematize this burgeoning conceptual and empirical terrain. We critically explore scholarship that examines resistance in terms of its manifestations and political intent or impact. We offer four fields of possibility for resistance scholarship: individual infrapolitics, collective infrapolitics, insubordination, and insurrection (the "four I's" of resistance). We conclude by considering the relationship between resistance theory and praxis, and pose four questions, or provocations, for stimulating future resistance research and practice.